Mud Crab (Scylla Serrata) Value Addition Analysis of Different Actors in Bangladesh (American Journal of Agricultural Science, Engineering, and Technology, 2021)
The mud crab business is being considered by most marketing operators to be a profitable and sustainable business due to the high demand in the international market. This study aims to determine value addition at different actors-based steps; primary data was collected from 100 respondents (40 collectors, 10 fatteners, 20 depot owners, 20 suppliers and 10 exporters) who were selected randomly from Khulna, Satkhira and Dhaka district. The mud crab analysis reveals that the value addition of the fatteners was the highest among all other intermediaries which was Tk. 11525 and Tk. 10665 per 100 kg of crab for the grade XXLPD in Khulna and Satkhira district respectively, whereas the lowest value addition was Tk. 1450 and Tk. 1090 per 100 kg of crab for grade KS3. The mentioned districts’ highest value addition by depot owners were Tk. 1191 and Tk. 1200 per 100 kg of crab for the grade FF1 respectively, while lowest value addition was Tk. 691 and Tk.750 per 100 kg of crab for the grade L and M, and by suppliers it was Tk. 2918 and 2758 per 100 kg of crab for the grade FF1. The range of value addition by exporters for Hong-Kong and Taiwan market was Tk. 260.25 to Tk. 13825 per 100 kg of crab. Value addition for exporting female crab to Taiwan market was greater than Hong-Kong market.